(untitled) (Asian Journal of Pharmaceutics (AJP), 2026)
The aim of the present investigation is to study the Isolation, Characterization, and in vitro Antioxidant Activity of Arjunolic Acid from Arjuna Bark. Materials and Methods: Fresh bark of Terminalia arjuna was collected from a natural habitat and authenticated by a qualified taxonomist. Powdered bark (1 kg) was defatted using petroleum ether (60–80°C) in a Soxhlet apparatus for 8 h. The defatted marc was extracted with methanol for 48 h. The extract was filtered and concentrated under reduced pressure using a rotary evaporator to obtain a crude methanolic extract. The ethyl acetate fraction was adsorbed onto silica gel and subjected to column chromatography using silica gel (60–120 mesh) as stationary phase and Chloroform: Methanol mixtures (95:5 → 80:20) as a Elution System. Fractions were monitored by thin layer chromatography (TLC) using chloroform: Methanol (9:1). Fractions showing identical spots were pooled and recrystallized using methanol to yield white crystalline arjunolic acid. Arjunolic acid was dissolved in methanol to obtain concentrations of 10, 25, 50, 75, and 100 μg/mL. Ascorbic acid was used as a reference standard at the same concentrations. The 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay was performed according to the method described earlier. Briefly, 1 mL of 0.1 mM DPPH solution was mixed with 1 mL of arjunolic acid at different concentrations. The mixture was incubated in the dark for 30 min and absorbance was measured at 517 nm. Results: High-performance TLC was performed using silica gel 60 F254 plates and a mobile phase of Toluene: Ethyl acetate: Methanol: Formic acid (6.5: 3.0: 0.5: 0.1 v/v/v/v). Both standard and isolated arjunolic acid exhibited a single compact band at Rf ≈ 0.45–0.46 after derivatization. Densitometric scanning at 540 nm confirmed peak overlap, verifying compound identity. Conclusion: The isolated arjunolic acid can serve as a reference marker for standardization and further pharmacological evaluation. The in vitro antioxidant evaluation confirmed that arjunolic acid possesses significant free radical scavenging and reducing properties.